Construct and content validity of the Functional Oral Intake Scale; Analyses from a cohort of patients with acquired brain injury. (28th July 2020) - Mortensen, Jesper; Pedersen, Asger Roer; Nielsen, Jørgen Feldbæk; Kothari, Mohit
ABSTRACT: Objective: To investigate the construct validity of the Functional Oral Intake Scale (FOIS) as a proxy measure for dysphagia, through associations with swallowing prerequisites, orofacial functions, age, and diagnosis; and to investigate content validity through distributions of FOIS ratings. Methods: A cohort of 1, 876 patients with severe acquired brain injury. Early Functional Abilities items were applied as measures of swallowing prerequisites and orofacial functions. Clustered logistic regression model with 6, 052 cross-sectional observations. Results: Disturbance in swallowing 10.55 OR (95%CI:7.90;14.09), oro-facial stimulation 3.04 OR (95%CI:2.41;3.83), and head control 2.86 OR (95%CI:2.25;3.62) were robustly associated with tube feeding (FOIS 1–3). Disturbance in trunk control, wakefulness, tongue movement/chewing, older age, and a non-stroke diagnosis were also associated with tube feeding. BMI did not attenuate associations in sensitivity analyses. FOIS ratings had greatest density in FOIS level 1 and level 7, with 25% and 40% of registrations, respectively. Level 4 was rated in only 1% of 6, 052 registrations. Conclusions: The FOIS was robustly associated with indicators of dysphagia. However, associations with postural control, wakefulness, age and diagnosis highlights that tube feeding may be attributed to other issues than dysphagia. It should be further investigated whether FOIS level 4 is meaningful in neurorehabilitation.